Influência do manganês no crescimento e na composição mineral de mudas de caramboleira - Hernandes, Amanda [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The star fruit tree presents good prospects of commercialization, due to the increasing demand for fruit, both in internal and external markets, being a promising option of cultivation. However, the main areas of star fruit production are located in regions characterized by acid soils, with low base saturation and often have aluminum and manganese in quantities high enough to limit the normal development of plants in general. The objective of this work was to evaluate the effects of manganese on growth and chemical composition of star fruit tree, as well as the dry mass of plants. The experimental design was a randomized block, consisted of 4 levels of Mn (0, 0.5, 25 and 50 mg Mn L-1), 4 times of collection (30, 60, 90 and 120 days of employment of the levels of Mn) and 3 replications, on seedlings conducted in nutrient solution. Biological and nutritional aspects of star fruit seedlings to identify the most appropriate level of Mn and its effects on growth of this fruitful were evaluated. The levels of Mn and times of collection influenced the contents of macro and micronutrients, the accumulation of elements and the dry mass depending of the organ examined. There was an increase in the efficiency of absorption of Mn with increasing levels, however, decrease the efficiency of transport and use of Mn. The biological parameters evaluated showed the highest average in the concentration of 0.5 mg L-1 Mn. Most of the manganese was determined in the residual fraction, giving an indication that the excess of manganese absorbed by the plant would be part of compounds, performing specific functions in star fruit tree and not free in the tissues.
Keywords: Averrhoa carambola; Fruitful; Micronutrientes; manganese; Carambola; Árvores frutíferas; Elementos traços na nutrição; Manganês